Investigation of post-earthquake displacements in viaducts using Geodetic and Finite Element Methods - Guney, D.; Acar, M.; Ozludemir, M. T.; Celik, R. N. (COPERNICUS GESELLSCHAFT MBH, 2010)
This paper presents the results of research into the post-earthquake displacements of the partially constructed road viaducts in Bolu, Turkey after the Izmit/Kocaeli, (M-w = 7.4), and Duzce (M-w = 7.1) earthquakes on 17 August and 12 November 1999, respectively. The investigations on the viaducts were carried out using both Geodetic and Finite Element Methods (FEM). Firstly, all the geodetic network stations selected for the project were checked because of the recent deformation in the area. Then, new control stations were placed between the piers of the viaducts. 28 object points were placed and measured on each pier to determine their displacements. In the second stage, the behaviours of the viaducts were modelled using the FEM, and the Duzce earthquake acceleration record was analysed to observe the response of the viaducts in a time history domain. The modelled displacement response of the viaducts was compared with the geodetic measurements in order to interpret the sensitivity of the design calculation of the engineering model. The pier displacements that were geodetically measured and calculated using FEM peak pier displacements showed an increase in the piers located closer to the surface rupture from the Izmit/Kocaeli and Duzce earthquakes. The agreement between the observed and modelled displacements decreases with the increase in the distance from the fault line. Since, near the fault trace the horizontal displacement field is discontinuous and large inelastic deformation is expected, the behaviour of the part of the structure located near the fault line cannot be easily reproduced by FEM simulations. This is because the applied model loads derived from the source acceleration spectra cannot be included in the localized finite deformation effects. In order to obtain an improved engineering analysis, it is necessary to utilise more parameters in the numerical analysis.
Keywords: NORTH ANATOLIAN FAULT; TURKEY; EARTHQUAKE; RUPTURE; IZMIT; BOLU; Geology; Meteorology & Atmospheric Sciences; Water Resources